The Application of Energy Management Systems Using the Internet of Things to Improve the Efficiency of Electrical Energy Usage in the MSMEs Sector - Sorongan, Erick; kango, riklan; Suhaedi, Suhaedi (Program Studi Teknik Elektro Universitas Khairun, 2023)
Monitoring the electrical energy of the MSME sector is necessary because the current use of electricity is less effective and consumes more electrical power. The use of electrical power can only be seen through the kWh meter measuring instrument and only shows the cumulative amount of electrical energy used. The analog panel design constraint only displays aggregate consumption data, not real-time. This study aims to develop an energy management system through Internet of Things communication for monitoring and controlling electrical devices in MSME sector buildings. Designer of a real-time measurement system that can read the parameters of the amount of electricity consumed so that MSME users can monitor the use of electricity consumption quickly and accurately via the internet and become a solution for more efficient monitoring work. The monitoring system is designed for load groups in buildings by using the ESP32 NodeMCU as a data processor for data received from the PZEM-004T sensor and sent directly to the Blynk server so that the data can be monitored and controlled on the Blynk interface via a smartphone. The data displayed on the Blynk application is in the form of voltage (volts), current (amperes), power (watts), electrical energy (kWh), and electricity usage rates in rupiah in real-time. The results of the study obtained show that the proposed method can read the energy consumption data of the electrical load used with an error value of 0.54% in voltage measurement and an error value of 2.93% in current measurement and has a delay in sending data to the monitoring application of an average of 3 seconds. The proposed draft Energy Management System can improve electricity efficiency if applied to solve the problem of electrical energy consumed in MSME sector buildings.